Collaborative studies on in vitro digestibility of dietary proteins based on the INFOGEST Quant protocol: toward international standardization - Lotti Egger; Ana Blanco-Doval; Cédric Brügger; Raquel Sousa; Lychou Abbühl; Marta Santos Hernández; Beatriz Miralles; Cristina Gómez-Marin; Adam Macierzanka; Patrycja Szumała; Ilona E. Kłosowska-Chomiczewska; Ana Isabel Mulet-Cabero; et al. (Food Research International, 2026)

Biogenic amine production and metabolic effects of Latilactobacillus curvatus in raclette-type cheese - Stefan Irmler; Charlotte Fleuti; Lotti Egger; Reto Portmann; Florian Loosli; Hélène Berthoud (International Dairy Journal, 2026)

Protecting lactoferrin for iron delivery: Effects of matrix composition and iron loading on gastric stability - Ana Blanco-Doval; Younas Dadmohammadi; Alireza Abbaspourrad; Claire E. Noack; Yunan Huang; Tiantian Lin; Lotti Egger; Michael B. Zimmermann; Reto Portmann (Food Hydrocolloids, 2026)

Mechanical cell disruption of the green microalga Chloroidium saccharophilum: Effects on protein digestibility and aroma profile - Daniel Kurpan; Xin Gao; Rodrigo Cardeiras; Mariluz Bagnoud-Velásquez; Lucie K. Tintrop; Christian Rhême; Cédric Brügger; Ana Blanco Doval; Reto Portmann; Lotti Egger; Fabian Wahl; Alexandra Baumeyer Brahier (Journal of Applied Phycology, 2026)
The efficiency and outcomes of mechanically disrupting microalgal cell walls depend on various factors and are case-specific. In general, bead milling is reproducible and scalable, and it can successfully increase the digestibility of microalgal biomass. However, its effects on the aroma of microalgal biomass have not yet been assessed. This study is the first to report the use of the NanoWitt-100 bead mill to break down microalgal biomass. Optimization of processing time and cell concentration revealed that the optimal conditions were a milling time of 15 min, and a cell concentration of 50 g L −1 . Under these conditions, we then compared the in vitro protein and amino acid digestibility as well as volatile organic compound (VOC) profiles of undisrupted and disrupted samples. Bead milling substantially increased total protein digestibility from 62.2 ± 2.28 to 99.7 ± 0.06%. The digestibilities of all amino acids and the in vitro digestible indispensable amino acid scores (DIAAS) also increased. Although the release of VOCs increased in the disrupted biomass, the VOC profiles indicated an improvement in the final aroma of the biomass. This outcome was due to a reduction in acid concentration and an increase in ester concentration as a proportion of the total VOCs. Overall, these findings support further scalability tests, sensory analysis, and in vivo trials using microalgae disrupted with the bead mill NanoWitt-100.

Predicting water activity in long-ripened cheeses using moisture, salt, free amino acids and lactate - Dominik Guggisberg; Reto Portmann; Lotti Egger; Remo S. Schmidt (International Dairy Journal, 2026)

Influence of processing on protein quality and environmental impact assessment of soy-based meat analogues - Laila Hammer; Corina Sägesser; Armin Siegrist; Mario Arcari; Moritz Goessler; Pornpimol Scheuchzer; Moritz Müller; Christoph Denkel; Joseph Dumpler; Alexander Mathys; Lotti Egger; Reto Portmann; et al. (Food Research International, 2025)

κ-casein genotypes and minerals in raw milk and their impact on coagulation properties - Dominik Guggisberg; Doris Zbinden; Nicolas Fehér; Lukas Eggerschwiler; Andreas Bosshart; Reto Portmann; Lotti Egger; Marlyse Raemy; Remo S. Schmidt (International Dairy Journal, 2025)

Impact of genetic κ-casein variants (A, B, E) on chymosin-induced milk coagulation properties: Application of a new LC–MS-based genotyping method - Dominik Guggisberg; Lotti Egger; Andreas Bosshart; Nicolas Fehér; Lukas Eggerschwiler; Remo S. Schmidt; Reto Portmann (International Dairy Journal, 2024)

In vitro DIAAS of Swiss soybean cultivars using the INFOGEST model: Increase in protein quality from soybean to soymilk and tofu - Laila Hammer; Diego Moretti; Claude-Alain Bétrix; Pabiraa Kandiah; Agostino Pellegri; Lychou Abbühl-Eng; Reto Portmann; Lotti Egger (Food Research International, 2024)

Ability of Latilactobacillus curvatus FAM25164 to produce tryptamine: Identification of a novel tryptophan decarboxylase - Stefan Irmler; Tharmatha Bavan; Eliane Binz; Reto Portmann (Food Microbiology, 2023)

A novel approach for the protein determination in food-relevant microalgae - Corina Sägesser; Johanna M. Kallfelz; Samy Boulos; Laila Hammer; Lukas Böcker; Reto Portmann; Laura Nyström; Alexander Mathys (Bioresource Technology, 2023)

A multi-centre peptidomics investigation of food digesta: current state of the art in mass spectrometry analysis and data visualisation - Reto Portmann; Pablo Jiménez-Barrios; Julien Jardin; Lychou Abbühl; Daniela Barile; Marianne Danielsen; Yu-Ping Huang; Trine Kastrup Dalsgaard; Beatriz Miralles; Valérie Briard-Bion; Stefano Cattaneo; Christophe Chambon; et al. (Food Research International, 2023)

Comparison of in vitro digestibility and DIAAR between vegan and meat burgers before and after grilling - Raquel Sousa; Reto Portmann; Isidra Recio; Sébastien Dubois; Lotti Egger (Food Research International, 2023)

In vitro digestibility of dietary proteins and in vitro DIAAS analytical workflow based on the INFOGEST static protocol and its validation with in vivo data - Raquel Sousa; Isidra Recio; Dominique Heimo; Sébastien Dubois; Paul J. Moughan; Suzanne M. Hodgkinson; Reto Portmann; Lotti Egger (Food Chemistry, 2023)

Structural model of the CopA copper ATPase of Enterococcus hirae based on chemical cross-linking - Mathias Lübben; Reto Portmann; Gerd Kock; Raphael Stoll; Malin M. Young; Marc Solioz (BioMetals, 2009)

CopY-like Copper Inducible Repressors are Putative ‘Winged Helix’ Proteins - Reto Portmann; Kristian R. Poulsen; Reinhard Wimmer; Marc Solioz (BioMetals, 2006)

Interaction kinetics of the copper-responsive CopY repressor with the cop promoter of Enterococcus hirae - Reto Portmann; David Magnani; Jivko V. Stoyanov; Ariane Schmechel; Gerd Multhaup; Marc Solioz (JBIC Journal of Biological Inorganic Chemistry, 2004)